2024
DOI: 10.1097/md.0000000000038274
|View full text |Cite
|
Sign up to set email alerts
|

Understanding tightened muscle in knee osteoarthritis and the impacts of Fu’s subcutaneous needling: A pilot trial with shear-wave elastography and near-infrared spectroscopy

Xiaolin Yang,
Hanlin Wang,
Jian Sun

Abstract: Background: Given the scarce reports on the interplay between Fu’s subcutaneous needling (FSN), tightened muscle, and therapeutic effects, we developed a clinical research protocol to synchronously collect data on clinical efficacy and muscle characteristics in patients with knee osteoarthritis, exploring the mechanism of FSN action. The primary aim was to assess the feasibility and safety of this protocol, guiding future trials and their sample size calculations. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
0
0
Order By: Relevance
“…Prior studies have suggested that the higher the value of the elastic modulus of the muscles around the knee, the higher the muscle tone and the tighter the epimysia, which results in restriction to the contraction of muscle fibers and function of the knee joint [ 34 – 36 ]. However, other studies have either failed to find significant results [ 37 ] or have reached contrary conclusions [ 38 ]. In response to these mixed findings, we investigate the elastic modulus of the major muscles along the force line of the lower extremity, aiming to provide credible evidence.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have suggested that the higher the value of the elastic modulus of the muscles around the knee, the higher the muscle tone and the tighter the epimysia, which results in restriction to the contraction of muscle fibers and function of the knee joint [ 34 – 36 ]. However, other studies have either failed to find significant results [ 37 ] or have reached contrary conclusions [ 38 ]. In response to these mixed findings, we investigate the elastic modulus of the major muscles along the force line of the lower extremity, aiming to provide credible evidence.…”
Section: Discussionmentioning
confidence: 99%